Kinerja Dinas Sosial dalam Sistem Layanan dan Rujukan Terpadu (SLRT) Terkait Program Penanggulangan Kemiskinan di Kota Denpasar - Agustina Daneswari, Ni Putu Wiwin; Yudartha, I Putu Dharmanu; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
The Government of Indonesia through the Ministry of Social established a integrated refferal service system (SLRT). The system is then developed into a integrated refferal service system. SLRT has been established in several cities or districts in Indonesia. One of them is the City of Denpasar formed the SLRT in 2017 which was organized by the Denpasar City Social Service. The theory used in this research is Agus Dwiyanto's theory of Performance such as indicators of productivity, service quality, responsiveness, responsibility, and accountability. The results showed that the performance of the Social Service in the Integrated Service and Referral System (SLRT) has gone well, but has not been optimal. There are people who have not recorded in DTKS, lack of sozialization, minimum number of PUSKESOS in desa/kelurahan, and human resources working to collect data in the field are still inadequate. Keywords: Performance, Integrated Service and Referral System (SLRT), Social Service, Poverty